2019
DOI: 10.1021/acs.jafc.9b03678
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation Profiles of Tristyrylphenol Ethoxylate Homologs in Lettuce under Greenhouse and Field Conditions

Abstract: Tristyrylphenol ethoxylates (TSPEOs) have been increasingly used in pesticide formulations as inert ingredients in China, but little information exists on the dissipation behavior of TSPEOs in foodstuffs. In this work, a rapid method for measuring TSPEO homologs in lettuce using QuEChERS and HPLC-MS/MS was established. This method was used to study the dissipation and distribution profiles of TSPEOs in lettuce. TSPEO homologs degraded rapidly under greenhouse and field conditions, with half-lives of 2.18–5.39 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…After 21 d, 96.1–99.8% of the initial residues of TSPEOn ( n = 6–29) were dissipated. The dissipation half-lives of homolog TSPEOn ( n = 6–29) and ΣTSPEOn were found to be slightly varied from 2.42 to 4.20 d, which were comparable to those in lettuce (1.82–4.34 d) and cucumber (1.80–4.30 d) in the previous studies ( 9 , 10 ), indicating that all the homolog TSPEOn ( n = 6–29) could be dissipated fast in these vegetables.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…After 21 d, 96.1–99.8% of the initial residues of TSPEOn ( n = 6–29) were dissipated. The dissipation half-lives of homolog TSPEOn ( n = 6–29) and ΣTSPEOn were found to be slightly varied from 2.42 to 4.20 d, which were comparable to those in lettuce (1.82–4.34 d) and cucumber (1.80–4.30 d) in the previous studies ( 9 , 10 ), indicating that all the homolog TSPEOn ( n = 6–29) could be dissipated fast in these vegetables.…”
Section: Resultssupporting
confidence: 81%
“…TSPEOn were relatively persistent in the field. It can be concluded that the cultivation system and plant type jointly affect the absorption and degradation of TSPEOn ( 9 , 10 ). Cowpea [Vigna unguiculata (L.) Walp.]…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study we therefore examined the formation and subsequent dissipation of residues of four different co‐formulants after PPP application on various vegetable crops and on apples under realistic field conditions 5 . Together with two further studies published around the same time, 6,7 this was the first instance when measured data on co‐formulant residues on plants grown under field conditions was published. Our study demonstrated that co‐formulants can form considerable amounts of residues directly after treatment in the field, i.e., in the low mg/kg range, but in general decline rapidly with half‐lives of few days, with wash‐off and volatilisation as the most probable major dissipation processes.…”
Section: Introductionmentioning
confidence: 98%
“…There are studies that evaluated the dissipation of selected co-formulants in fruits or vegetables. For instance, one study developed a method for measuring the dissipation of tristyrylphenol ethoxylates in lettuce by liquid chromatography (LC) coupled to single quadrupole (Q) (Li et al, 2020). Another study selected four co-formulants (di-2-ethylhexyl sulfosuccinate, sodium dodecyl sulfate, dimethyl naphthalene sulfonate sodium salt and N,N-dimethyldecanamide), and evaluated their degradation in vegetables and apples under field conditions by LC-tandem mass spectrometry (LC-MS/MS) system (Balmer et al, 2020).…”
Section: Introductionmentioning
confidence: 99%